Acquired and Inherited Zinc Deficiency-Related Diseases in Children: A Case Series and a Narrative Review - Tommaso Bellini; Marta Bustaffa; Barbara Tubino; Benedetta Giordano; Clelia Formigoni; Elena Fueri; Federica Casabona; Barbara Vanorio; Andrea Pastorino; Astrid Herzum; Caterina Matucci-Cerinic; Serena Arrigo; et al. (MDPI AG, 2024)
Zinc deficiency is a significant global health concern among children, manifesting in various acquired and inherited conditions. This comprehensive overview of acquired and inherited zinc deficiency-related diseases in children aimed to explore the clinical presentations, diagnostic challenges, and management strategies associated with these conditions. This case series elucidates the diverse clinical manifestations of zinc deficiency in pediatric patients, ranging from dermatitis and growth retardation to immune dysregulation and neurological abnormalities, and discusses the underlying genetic mechanisms, clinical phenotypes, and therapeutic interventions. The complexity of zinc deficiency-related diseases in children underscores the need for a multidisciplinary approach involving pediatricians, dermatologists, geneticists, and nutritionists to optimize patient care and outcomes.